The Mediterranean Sea : Temporal Variability and Spatial Patterns. - Borzelli, Gian Luca Eusebi (Geophysical monograph, 2014)
Surface, intermediate, and deep-water processes and their interaction in time and space drive the major ocean circulation of the Mediterranean Sea. All major forcing mechanisms, such as surface wind forcing, buoyancy fluxes, lateral mass exchange, and deep convection determining the global oceanic circulation are present in this body of water. Deep and intermediate water masses are formed in different areas of the ocean layers and they drive the Mediterranean thermohaline cell, which further shows important analogies with the global ocean conveyor belt. The Mediterranean Sea: Temporal Variabi.